ANALISIS YURIDIS TERHADAP MAHAR YANG TERHUTANG SAMPAI TERJADI PERCERAIAN (Studi Putusan Mahkamah Syar’iyah Bireuen Nomor: 178/Pdt-G/2013/MS-Bir) - ERY NOOR (PREMISE LAW JURNAL, 2017)
A marriage with owed dowry in the Islamic law is legitimate when it fulfills all marriage requirements. The obligation of giving dowry is not the requirement in a marriage. An owed dowry does not affect the validity of a marriage, but it has to be given by a husband to his wife. Some factors which cause a husband not to give a dowry to his wife are as follows: first, economic factor in which a man with low income feels that he cannot afford to provide dowry. Secondly, it is a socio-cultural reason in which the value of dowry in the Acehnese culture is a symbol of honor and prestige for both families. For the women’s side, the high value of dowry indicates her social position. Thirdly, a husband’s lack of kno9wledge of dowry; if later on it is paid off, it is by the court’s verdict and not by the husband’s willingness. The Panel of Judges also consider that the complaint about dowry as the result of divorce is a kind of judgment toward the wife by providing protection and increasing a woman’s dignity in getting her right for dowry. Keywords: Owed Dowry, Marriage